Seeing yourself strangely: Media mirroring in Takehito Etani's The Third Eye Project. Issue 2 (1st December 2014) - Pasek, Anne
A long history of technologies and techniques in media art seek to make the body strange through its mediated self-perception. Traditionally, scholars have viewed these works as enframing or narcissistic gestures, however, it does not necessarily follow that this bodily strangeness is inherently negative, or even new. By viewing the body's phenomenology as inextricably tied to technological supports, the extent to which technological forms of self-perception are necessarily enframing can be constructively critiqued. This suggestion is explored through an analysis of Takehito Etani's The Third Eye Project (2002), a performance prosthetic that presents its users with a live video feed of their own back from a third-person avatar perspective. The mediation of self-perception in this piece, both internally and technologically, suggests an alternative outlook to this genre of media art: one that takes the strangeness of the self as inherent to self-perception both in and outside of technology.